Quantitative assessment of demyelination in ischemic stroke in vivo using macromolecular proton fraction mapping; Journal of Cerebral Blood Flow and Metabolism; Vol. 38, iss. 5 - Khodanovich M. Yu. Marina Yurjevna; Kisel A. A. Alena Andreevna; Akulov A. E. Andrey Evgenjevich; Atochin D. N. Dmitry Nikolaevich; Kudabaeva M. S. Marina Stanislavovna (2018, 2018)
Title screen